2020
DOI: 10.1038/s41598-020-71851-9
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of OsACBP5 protects transgenic rice against necrotrophic, hemibiotrophic and biotrophic pathogens

Abstract: The most devastating diseases in rice (Oryza sativa) are sheath blight caused by the fungal necrotroph Rhizoctonia solani, rice blast by hemibiotrophic fungus Magnaporthe oryzae, and leaf blight by bacterial biotroph Xanthomonas oryzae (Xoo). It has been reported that the Class III acyl-CoA-binding proteins (ACBPs) such as those from dicots (Arabidopsis and grapevine) play a role in defence against biotrophic pathogens. Of the six Arabidopsis (Arabidopsis thaliana) ACBPs, AtACBP3 conferred protection in transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 151 publications
(195 reference statements)
1
26
0
Order By: Relevance
“…Inoculation of cultivar Conrad with P. sojae revealed that most members of Classes I, III, and IV exhibited slight downregulation in expression from the control. This situation appeared to differ from ACBPs of other plants such as Arabidopsis, grapevine and rice, in which Class III ACBPs, AtACBP3 ( Xiao and Chye, 2011 ), VvACBP ( Takato et al, 2013 ), and OsACBP5 ( Panthapulakkal Narayanan et al, 2020 ) respectively, respond to plant pathogens. In transgenic Arabidopsis, AtACBP3 -overexpressors and acbp3 showed contrasting reactions to biotrophic and necrotrophic pathogens.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Inoculation of cultivar Conrad with P. sojae revealed that most members of Classes I, III, and IV exhibited slight downregulation in expression from the control. This situation appeared to differ from ACBPs of other plants such as Arabidopsis, grapevine and rice, in which Class III ACBPs, AtACBP3 ( Xiao and Chye, 2011 ), VvACBP ( Takato et al, 2013 ), and OsACBP5 ( Panthapulakkal Narayanan et al, 2020 ) respectively, respond to plant pathogens. In transgenic Arabidopsis, AtACBP3 -overexpressors and acbp3 showed contrasting reactions to biotrophic and necrotrophic pathogens.…”
Section: Discussionmentioning
confidence: 73%
“…tomato DC3000, but was susceptible to infection by necrotrophic fungus Botrytis cinerea ( Xiao and Chye, 2011 ). In contrast, transgenic rice OsACBP5 -overexpressors displayed disease resistance toward biotrophic ( Xanthomonas oryzae ), hemibiotrophic ( Magnaporthe oryzae and Fusarium graminearum ) and necrotrophic ( Rhizoctonia solani and Cercospora oryzae ) pathogens via both jasmonic acid (JA)- and salicylic acid (SA)-mediated pathways ( Panthapulakkal Narayanan et al, 2020 ). Also transgenic Arabidopsis overexpressing V. vinifera Class III ACBP was tolerant to P. syringae and Colletotrichum higginsianum , a pathogenic hemibiotrophic ascomycetous fungus ( Takato et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It binds long-chain acyl-CoA esters [ 83 ], participates in acyl-CoA transport [ 84 ], maintains acyl-CoA pool [ 85 ], and regulates the activities of various enzymes including glycerol-3-phosphate acyltransferase [ 83 ], lysophosphatidylcholine acyltransferase [ 85 ] and lysophosphatidic acid acyltransferase [ 86 ]. The transport of acyl-CoA esters is important for the biosynthesis of lipids such as glycerolipids, ceramides and phospholipids, and studies have shown that the binding of phospholipids to ACBPs plays a role in plant growth and development as well as stress responses [ 76 , 78 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Following the discovery of BnACBP, similar 10-kDa ACBPs emerged in Arabidopsis thaliana [ 95 ], Gossypium hirsutum (cotton) [ 96 ], Ricinus communis (castor bean) [ 97 ], Digitalis lanata Ehrh.…”
Section: Plant Acbpsmentioning
confidence: 99%
“…Thus far, only AtACBP2 interacts with FARNESYLATED PROTEIN6 (AtFP6) which may be involved in phospholipid repair following heavy metal-induced lipid peroxidation [ 75 ]. Lipid binding of ACBPs and their protein-protein interactions are now known to be important in regulating abiotic and biotic stress responses [ 74 , 75 , 76 , 78 , 80 , 87 , 88 , 93 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ], as well as plant development including embryogenesis [ 81 , 116 , 119 ], seed dormancy [ 78 ], seed germination and development [ 78 , 80 , 129 , 130 , 131 ], cuticle development [ 25 , 26 ], pollen growth [ 132 ] and senescence [ 112 , 117 ].…”
Section: Plant Acbpsmentioning
confidence: 99%
See 1 more Smart Citation